A Comparison of the Touwen Infant Neurological Examination, General Movement Assessment and Alberta Infant Motor Scale in Infants Born Preterm - Atcı, Merve; Porsnak, Doğan; Alkan, Halil; Mutlu, Akmer (My University, 2025)
Objective: Infants born preterm are known to be at risk of moderate to severe developmental problems. The study aimed to compare Touwen Infant Neurologic Examination (TINE), General Movement Assessment (GMA) and Alberta Infant Motor Scale (AIMS) scores assessed on the same day at 3-to-5 months-of-corrected-age in infants separated by gestational week. Materials and Methods: We included a total of 78 infants with a history of preterm birth, as very preterm (<32 weeks, n = 26), moderate preterm (320/7 to 336/7 weeks, n = 30) and late preterm (340/7 to 366/7 weeks, n = 22), at 3 to 5 months-of-corrected-age. The study compared the results of TINE, AIMS and GMA in preterm infants separated by gestational age, and analysed AIMS scores according to GMA results. In addition the association between TINE and AIMS scores was assessed. Results: There was statistical significance between the prone motor performances of the groups, due to the statistical difference between infants born late preterm and infants born very preterm; the prone motor performance of infants born late preterm was significantly higher than infants born very preterm. Infants with normal fidgety movements had higher prone (p=0.043) and supine (p= 0.037) motor performance scores than infants with aberrant fidgety movements. A significant negative low correlation was found between TINE findings and total AIMS scores. Conclusions: Infants with absent and abnormal fidgety movements have lower AIMS score and gestational age might affect AIMS score. Additionally, it has been showed that abnormal neurologic findings, according to TINE, are negatively related to AIMS score.
Keywords: Preterm, General movements, Minor Neurological Dysfunction